Objective cardiology [electronic resource] - Chandra, Mahesh (New Age International (P) Ltd, Publisher, 2009)
In an era of super-specialization almost every postgraduate student harbors a desire of acquiring training in a specialized way. This book contains MCQs for DM entrance exams.